DEVELOPMENT OF A PORTABLE SAWMILL FOR THE SMALL RURAL PROPERTY - BERTINATTO, R.; BREDA, C. A.; BARICCATTI, R.; VIDAL, T. C. M.; WERNCKE, I.; MAXIMO, C. C. (Revista Brasileira de Engenharia de Biossistemas, 2012)
The fast forest production growth in Brazil has revealed the small producers’ difficulty in processing the planted trees small quantities in their properties, due to high wood cutting and transportation costs when taking it to the sawmill, which is usually made by outsource, and, because of this, the producer profits are always depending on these services payment. This context has encouraged this research, which had as its objective the building of a portable chainsaw, with low production costs and that makes use of a chainsaw usually already owned by the producer who will work with it. It was made in Cascavel city, Paraná state, in 2009. The machine was complemented with the installation of a silencer, in order to decrease the noise and target the exhaust gas away from the operator’s face, in addition to a traction set with a tirfor hoist to decrease the effort made by him as well. In the operation evaluation, the cutting quality was satisfying and the complements have contributed in a meaningful way to improve the profits, as well as there was a smaller operator’s exhaustion. However we concluded that this sawmill model is indicated to the processing of small wood quantities due to the reasonable ergonomics and the intense need to work near to the ground level.